Peran Guru dalam Meningkatkan Minat dan Prestasi Siswa dalam Pembelajaran Bahasa Arab - Aisyah; Muhammad Rido’i (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Nurul Hakim, 2024)
This study investigates the role of Fus'ha (Modern Standard Arabic) and local dialects in Arabic language education, focusing on the integration of both forms in various educational contexts in Egypt, Morocco, Lebanon, and the United Arab Emirates. Data was collected through in-depth interviews, classroom observations, and document analysis from several educational institutions. The findings reveal that a balanced approach incorporating both Fus'ha and dialects significantly enhances linguistic competence and social integration. However, challenges such as insufficient teaching materials for dialects and differing perceptions about their importance persist. Technology and cultural integration emerge as crucial tools in addressing these challenges. The study highlights the need for comprehensive curricula, innovative pedagogical strategies, and further research to develop effective teaching materials and understand long-term impacts on learners' linguistic and communicative abilities. By adopting a holistic approach that values linguistic and cultural diversity, Arabic language education can be made more effective and meaningful.